Stress State and its Definition in Hardfacing Heat-Resistant Steel Cold Rolling Mill Rollers; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Valuev D. V. Denis Viktorovich (Engineering of Machines and Mechanisms, 2014)
Title screen